THE CORRELATION BETWEEN STUDENTS’ GRAMMATICAL KNOWLEDGE AND THE ABILITY IN TRANSLATING INDONESIAN-ENGLISH NARRATIVE TEXTS BY THE SECOND YEAR STUDENTS OF SMAN 1 SENTAJO RAYA - Rise Desva Sari; Fadly Azhar; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to find out the significant correlation between students’ grammatical knowledge and the ability in translating Indonesian-English narrative texts by the second year students of SMAN 1 Sentajo Raya. The correlational research was used to find out the relationship between two variables or it called bivariate correlation. To collect the data in this research two tests were used. A simple random sampling technique is used to determine the sample of the research. There were 40 students participating in this research. Narrative text was used to know the students' translation ability and past tenses test was used to know students’ grammatical knowledge. The result of the study shows that the correlation between two variables are significantly correlated. As a means there is a significant a significant correlation between students’ grammatical knowledge and the ability in translating Indonesian-English narrative texts by the second year students of SMAN 1 Sentajo Raya. In other words, there is an influence of students’ grammatical knowledge towards students’ ability in translating Indonesian-English narrative texts. The finding could important distributions to both teaching translation and grammar, especially the relationship between the two variables.Key Words: Correlation, Grammatical Knowledge, Translation